UPAYA PENINGKATAN KESEHATAN JIWA MASYARAKAT MELALUI COMMUNITY MENTAL HEALTH NURSING DI KOTA PADANG TAHUN 2021 - Heppi Sasmita; Defia Roza; Sila Dewi Anggeini (P3M Universitas Aisyiyah Surakarta, 2023)
Mental health is self-control in dealing with stressors in the surrounding environment by always thinking positively in harmony without any physical and psychological pressure, both internally and externally that leads to emotional stability. One of the problems that occur in mental health is a psychosocial problem in the form of anxiety. Anxiety often occurs because of excessive anxiety with the condition you have, the same thing often happens to people with non-communicable diseases. One solution to the problem in this case is to do CMHN. The purpose of this community service is to increase community independence in tackling mental health problems in the city of Padang. The method used is in the form of socializing mental programs to community leaders, providing training to mental health cadres (KKJ) on early detection, home visits and mobilizing the community and health education to the community about non-communicable diseases. The conclusions obtained were that there was an increase in cadre knowledge after the action and the results of early detection of the 1403 population there were 1% (23 people) with mental disorders, 12% (164 people) with the risk of psychosocial problems and the rest (87%) were mentally healthy.